If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2b=-3b+16
We move all terms to the left:
-2b-(-3b+16)=0
We get rid of parentheses
-2b+3b-16=0
We add all the numbers together, and all the variables
b-16=0
We move all terms containing b to the left, all other terms to the right
b=16
| m+1.3=-1.4 | | 211=92-w | | 3-3r=10-2r | | 3u+14=u-16-7 | | 3u+13=u−16−7 | | 5x-15=3×+10 | | 4x^2+24x+160=0 | | 13j+10=14j+5 | | 1-r+5=2 | | −5(3x−15)=2(x−19)−23 | | 8.95+6.1k=-18.77-5.7k+10.4k | | 5x-5x+14=8 | | 12(x−12)=9+8x | | 17y+5=7.9 | | 10+3x=2(−x+3)−11 | | 254-u=64 | | m(-3)=11 | | -1/4+3/5x=-1/3 | | 8.95+6.1k=-18.77−5.7k+10.4k | | 8m+3m=11 | | 2+18q=17+17q | | −4.3g=25.8g= | | 166-u=293 | | 20+9n+4n=3+12n | | |2x+3|-5=8 | | 13h=14+12h | | 169=-v+213 | | 34=y-15 | | -6a=2-8a | | -10-10d=10d+10 | | 7n+3.7n-6.6=-13 | | 13/24=7/8x-5/6 |